Cilomilast Ameliorates Renal Tubulointerstitial Fibrosis by Inhibiting the TGF-β1-Smad2/3 Signaling Pathway - Xu, Man; Li, Shumin; Wang, Jiajia; Huang, Songming; Zhang, Aihua; Zhang, Yue; Gu, Wei; Yu, Xiaowen; Jia, Zhanjun (Frontiers in Medicine, 2021)
Background: Renal tubulointerstitial fibrosis is the key pathological feature in chronic kidney diseases (CKDs) with no satisfactory therapies in clinic. Cilomilast is a second-generation, selective phosphodiesterase-4 inhibitor, but its role in renal tubulointerstitial fibrosis in CKD remains unclear. Material and methods: Cilomilast was applied to the mice with unilateral ureteric obstruction (UUO) and renal fibroblast cells (NRK-49F) stimulated by TGF-β1. Renal tubulointerstitial fibrosis and inflammation after UUO or TGF-β1 stimulation were examined by histology, Western blotting, real-time PCR and immunohistochemistry. KIM-1 and NGAL were detected to evaluate tubular injury in UUO mice. Results: In vivo, immunohistochemistry and western blot data demonstrated that cilomilast treatment inhibited extracellular matrix deposition, profibrotic gene expression, and the inflammatory response. Furthermore, cilomilast prevented tubular injury in UUO mice, as manifested by reduced expression of KIM-1 and NGAL in the kidney. In vitro, cilomilast attenuated the activation of fibroblast cells stimulated by TGF-β1, as shown by the reduced expression of fibronectin, α-SMA, collagen I, and collagen III. Cilomilast also inhibited the activation of TGF-β1-Smad2/3 signaling in TGF-β1-treated fibroblast cells. Conclusion: The findings of this study suggest that cilomilast is protective against renal tubulointerstitial fibrosis in CKD, possibly through the inhibition of TGF-β1-Smad2/3 signaling, indicating the translational potential of this drug in treating CKD.